ENT530: Blastmaster (M) Sdn Bhd / Engku Aimi Engku Mohamad Nor Azlan, Nur Syahirah Shahrin and Zuraimah Zomadi - Engku Mohamad Nor Azlan, Engku Aimi; Shahrin, Nur Syahirah; Zomadi, Zuraimah (2017)
Blast Master Malaysia Sdn Bhd is the one of the biggest company that specialized in fireworks and Pyrotechnics Company in Malaysia. This company incorporated on 8th August 1989 and located in Ampang, Selangor. This company is specializing in creating fireworks, pyrotechnics, disposal, demolition, and blasting ammunition and special effects. They have team of experts in choreographing, customizing fireworks and pyrotechnics effects in unique way depends on the event .Beside, they also have experience specialist to assist in the ordinance projects. Blast Master Malaysia Sdn Bhd customer is including Government and private sector. The mission of this company is to become a leader in Malaysia fireworks industry while their vision is to be global which a hub in import and export of fireworks internationally.